Exercise-provoked esophageal motility disorder in patients with recurrent chest pain - Budzyński, Jacek (Baishideng Publishing Group Co., Limited, 2010)
AIM: To investigate the relationship between exercise-provoked esophageal motility disorders and the prognosis for patients with chest pain. METHODS: The study involved 63 subjects with recurrent angina-like chest pain non-responsive to empirical therapy with proton pump inhibitor (PPI). In all, a coronary artery angiography, panendoscopy, 24-h esophageal pH-metry and manometry, as well as a treadmill stress test with simultaneous esophageal pH-metry and manometry monitoring, were performed. Thirty-five subjects had no significant coronary artery lesions, and 28 had more than 50% coronary artery narrowing. In patients with hypertensive esophageal motility disorders, a calcium antagonist was recommended. The average follow-up period was 977 ± 249 d. RESULTS: The prevalence of esophageal disorders, such as gastroesophageal reflux or diffuse esophageal spasm, was similar in patients both with and without significant coronary artery narrowing. Exercise prompted esophageal motility disorders, such as a decrease in the percentage of peristaltic and effective contractions and their amplitude, as well as an increase in the percentage of simultaneous and non-effective contractions. In 14 (22%) patients the percentage of simultaneous contractions during the treadmill stress test exceeded the value of 55%. Using Kaplan-Meier analysis and the proportional hazard Cox regression model, it was shown that the administration of a calcium channel antagonist in patients with such an esophageal motility disorder significantly decreased the risk of hospitalization as a result of a suspicion of acute coronary syndrome after the 2.7-year follow-up period. CONCLUSION: In patients with chest pain non-responsive to PPIs, a diagnosis of exercise-provoked esophageal spasm may have the effect of lowering the risk of the next hospitalization.